Immunization with DNA vectors consisting of selected Dengue 2 virus genes stimulated antibody Responses in Mice - Shafee, N.; AbuBakar, Sazaly (2006)
Dengue virus Type 2 C, prM, truncated E (NB-E and B-E), NS1, NS2A, NS2B/3 and NS3 genes were cloned and expressed using the pEGFP-N1 eukaryotic expression vector. Protein expression was visualized in transfected Vero cell cultures. Immunogenicity of the recombinant DNA plasmids was determined by inoculating 8 weeks old BALB/cJ mice with two doses of plasmid cocktail followed by a booster inoculation at two weeks apart. Mice were also injected with empty vector plasmids or vaccinated with virus inoculum as controls. Initial inoculation with the plasmid cocktail resulted in IgG response comparable to inoculation with virus inoculum alone which peaked after the booster dose. Rapid rise in IgG response was also observed when the mice were subsequently challenged with partially purified dengue virus Type 2, ten weeks after the first inoculation. These results suggest for the first time, that dengue virus DNA genes expressing antigens as fusion proteins with EGFP could stimulate immune responses in vivo.